2004
DOI: 10.1021/la035929m
|View full text |Cite
|
Sign up to set email alerts
|

Particle-Induced Phase Separation in Quasi-Binary Polymer Solutions

Abstract: A long-ranged attractive force was recently detected between two mica plates immersed in a quasibinary polymer solution (Freyssingeas et al. Langmuir 1998, 14, 5877-5889). The quasi-binary polymer solution was aqueous ethyl(hydroxyethyl)cellulose (EHEC), where the EHEC had a broad polydispersity. The long-ranged attractive force in the EHEC solution could not be attributed to classical mechanisms such as depletion or bridging. In this study, we investigated if this attractive force can give rise to instability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…A third possible scenario in adsorbing polymer−particle mixtures is a capillary-induced phase separation (CIPS). CIPS has recently been discovered in polymer solutions that are close to phase separation even in the absence of particles. The basic physics of a CIPS is that a new phase, the “capillary phase”, can be formed in the gap between the colloidal particles, if the interfacial free energy between the capillary phase and the particle surface is lower than between the original “reservoir phase” and the surface .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A third possible scenario in adsorbing polymer−particle mixtures is a capillary-induced phase separation (CIPS). CIPS has recently been discovered in polymer solutions that are close to phase separation even in the absence of particles. The basic physics of a CIPS is that a new phase, the “capillary phase”, can be formed in the gap between the colloidal particles, if the interfacial free energy between the capillary phase and the particle surface is lower than between the original “reservoir phase” and the surface .…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this work is to model how the phase behavior of a polymer solution is affected by added particles to which the polymer adsorbs. Previously, an experimental study from our group has shown that added particles enhance the phase separation in aqueous solutions of ethyl(hydroxyethyl)cellulose (EHEC) . In the latter experiments, EHEC adsorbed to the particles but the polymer-to-particle ratio was high, making bridging unlikely as the destabilizing mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…For EHEC, Malmsten and Tiberg [11] showed that EHEC adsorb onto macroscopically polystyrene surfaces. It is evident that EHEC adsorbs onto PSL particles [12,13]. For CMC, Wallström et al [12] concluded from viscosity measurements that CMC does not adsorb onto PSL particles, which was in accordance to a more systematic study of Backfolk [14] giving that CMC does not adsorb onto latex particles based on other types of polymers than polystyrene.…”
Section: Introductionmentioning
confidence: 66%
“…The degrees of substitution were previously determined using gas chromatography. 5 The numbers for these are given as DS ethyl and MS EO , referring to the average number of substituents per glucose unit of the cellulose backbone. The only difference in structure between EHEC and HM-EHEC is that a few hydrophobic grafts are introduced onto the cellulose backbone in HM-EHEC.…”
Section: Methodsmentioning
confidence: 99%
“…5 The molecular weights and the polydispersity indexes were determined by size exclusion chromatography. 5 The molecular weights of EHEC and HM-EHEC were approximately 5 · 10 5 Da, and the polydispersity indexes are M w /M n » 6 for both polymers (Table 1).…”
Section: Methodsmentioning
confidence: 99%